Anaphylaxis to Iodinated Contrast Media: Clinical Characteristics Related with Development of Anaphylactic Shock - Kim, Min-Hye (Public Library of Science, 2014)
OBJECTIVE: Anaphylaxis is the most severe form of radiocontrast media (RCM) induced hypersensitivity and can be life-threatening if profound hypotension is combined. With increased use of iodine based RCM, related hypersensitivity is rapidly growing. However, the clinical characteristics and risk factors of RCM induced anaphylaxis accompanied by hypotension (anaphylactic shock) are not clearly defined. This study was performed to investigate the risk factors of RCM induced anaphylactic shock and the clinical value of RCM skin testing to identify causative agents in affected patients. METHODS: We analyzed the data of RCM induced anaphylaxis monitored by an inhospital pharmacovigilance center at a tertiary teaching hospital from January 2005 to December 2012 and compared the clinical features and skin test results according to the accompanying hypotension. RESULTS: Among total of 104 cases of RCM induced anaphylaxis, 34.6% of patients, developed anaphylaxis on their first exposure to RCM. Anaphylactic patients presenting with shock were older (57.4 vs. 50.1 years, p = 0.026) and had a history of more frequently exposure to RCM (5.1±7.8 vs. 1.9±3.3, p = 0.004) compared to those without hypotension. Among RCMs, hypotension was more frequent in anaphylaxis related to iopromide compared to other agents (85.0% vs. 61.4%, p = 0.011). Skin tests were performed in 51 patients after development of RCM induced anaphylaxis. Overall skin test positivity to RCM was 64.7% and 81.8% in patients with anaphylactic shock. CONCLUSION: RCM induced anaphylactic shock is related to multiple exposures to RCM and most patients showed skin test positivity to RCM.